The folk of the faraway tree - Blyton, Enid (London: Hodder children books ., 2020)
Stuck-up Connie refuse to believe in the faraway tree, until Joe, Beth and Frannie take her to the Land of Secrets and The Land of Treats! But then the tree starts dying, and nobody knows what's wrong. How can they save the magical faraway tree?
Keywords: English - Fiction Book